Social Conflict in the Film Komang by Naya Anindita: Perspective of Lewis A. Coser - Nindy Dian Carmelita; Heny Subandiyah (Raja Zulkarnain Education Foundation, 2026)
According to Lewis A. Coser, open conflict is more common in societies that have partial or non-intimate relationships. Individuals or groups without involving deep emotions or total hostility. This study aims to describe the forms of social conflict in the film Komang by Naya Anindita from Lewis A. Coser's perspective, which include realistic social conflict, non-realistic social conflict, and the positive function of social conflict. This study uses a qualitative descriptive method with a sociological literary approach. The data source used is the film Komang by Naya Anindita. The data are in the form of dialogue quotes, sentences, paragraphs, accompanied by images containing realistic social conflict, non-realistic social conflict, and the positive function of social conflict. The data collection process used is listening, reading, and recording with coding through observation guide instruments. Data on the forms of social conflict in the film Komang were analyzed using the Miles and Huberman model analysis technique. The data validity technique uses a credibility test of persistence with peer discussions. The results of this study indicate the existence of: 1) realistic social conflict, the existing conflict is in the form of religious differences; lack of attention from partners; uncertainty and expectations of a relationship; 2) non-realistic conflict in the form of feelings of offense; past trauma; jealousy; 3) the positive function of existing social conflict in the form of tolerance of diversity, enthusiasm for achieving ideals, respecting and honoring fellow human beings, and upholding solidarity.